Uji Angka Lempeng Total (ALT) dan PH pada Produk Inovasi Minuman Probiotik Jalembi (Jambu Merah, Lemon, Melon, Bit) dengan Starter Lactobacillus plantarum - Reza Anindita; Afrinia Eka Sari (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2023)
One of the causes of the failure of anemia prevention therapy in pregnant women with the potential for stunting is the side effects of nausea and vomiting from Blood Supplement Tablets so most pregnant women choose not to consume iron supplements given by the government for free. This has opened up opportunities for the discovery of product innovations for probiotic drinks from jalembi juice (red guava, lemon, melon, beetroot) with a starter Lactobacillus plantarum to be developed as a candidate for a health drink to replace anti-anemia anemia for pregnant women. The purpose of this study was to test the total lactic acid bacteria (LAB), pH, and temperature of jalembi juice probiotic drink with L. plantarum starter. This research method was carried out by calculating the total amount of LAB of L. plantarum using the Total Plate Count (TPC), pH, and temperature of the jalembi juice probiotic drink. Data analysis was carried out using a quantitative descriptive approach. The results of this study indicated that the total LAB of L. plantarum contained in the jalembi juice probiotic drink was 1.7 x 108 CFU/ml with an average pH and temperature of 3.38 and 22.4 ºC respectively. This study concludes that the total LAB in the jalembi juice probiotic drink with L.plantarum starter according to the recommended standards can have an effect on body health, which is around 108 -109 CFU/ml.